Food-Based Science Curriculum Yields Gains in Nutrition Knowledge - Carraway-Stage, Virginia; Hovland, Jana; Showers, Carissa; Díaz, Sebastián; Duffrin, Melani W. (The Journal of school health, 2015)
ABSTRACT BACKGROUND Students may be receiving less than an average of 4 hours of nutrition instruction per year. Integrating nutrition with other subject areas such as science may increase exposure to nutrition education, while supporting existing academics. METHODS During the 2009‐2010 school year, researchers implemented the Food, Math, and Science Teaching Enhancement Resource (FoodMASTER) Intermediate (FMI) curriculum in 18 fourth‐grade classrooms, whereas 16 classrooms served as comparison. FMI is a hands‐on, integrative curriculum for children in grades 3‐5 that uses food as a tool to teach mathematics and science. Researchers developed a 28‐item multiple‐choice questionnaire to assess students' nutrition knowledge in 6 content areas. Students were evaluated at baseline and post‐intervention. Data were analyzed using independent t tests. Analysis of covariance was employed to control for differences at baseline when assessing the effectiveness of the FMI curriculum to increase nutrition knowledge. RESULTS A significant improvement was observed in total nutrition knowledge at post‐intervention (adjusting for baseline) between groups (F [1] = 128.95; p < .01) and in all content areas post‐intervention. CONCLUSIONS Findings from this study suggest teachers were successfully able to integrate science and nutrition to meet multiple academic standards. More specifically, results showed implementation of the integrative FMI curriculum effectively improved fourth‐graders' nutrition knowledge compared with students not exposed to FMI.